Empowering Pre-Service English Teachers Through AI-Based Lesson Design: A Case Study on Curipod - Normuminov, Murod (Universitas Andalas, 2025)
This study investigates the use of Curipod, an AI-powered lesson design tool, in developing planning competence among pre-service English language teachers. Situated within the “Teachnology” training program in Uzbekistan, the study involved six trainees who used Curipod to design and deliver interactive 30-minute demo lessons. Drawing on lesson plan evaluations, reflections, and observer notes, the study found that Curipod enhanced the structural quality of lessons, reduced planning anxiety, and encouraged creative integration of multimodal elements. Trainees reported improved confidence in organizing content, timing tasks, and aligning objectives with classroom activities. However, challenges included overreliance on AI templates and occasional mismatches in content relevance. The findings highlight Curipod’s role as a digital scaffold, supporting pedagogical thinking without replacing the teacher’s role. Implications for teacher education include integrating reflective tasks on AI use, promoting critical digital literacy, and ensuring contextual and cultural adaptation of AI-generated content. The study contributes to growing research on AI in ELT, offering practical recommendations for using generative tools in teacher preparation programs.